2024
DOI: 10.3389/fphar.2024.1364135
|View full text |Cite
|
Sign up to set email alerts
|

Breaking genetic shackles: The advance of base editing in genetic disorder treatment

Fang Xu,
Caiyan Zheng,
Weihui Xu
et al.

Abstract: The rapid evolution of gene editing technology has markedly improved the outlook for treating genetic diseases. Base editing, recognized as an exceptionally precise genetic modification tool, is emerging as a focus in the realm of genetic disease therapy. We provide a comprehensive overview of the fundamental principles and delivery methods of cytosine base editors (CBE), adenine base editors (ABE), and RNA base editors, with a particular focus on their applications and recent research advances in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 380 publications
(506 reference statements)
0
1
0
Order By: Relevance
“… 8 , 9 Besides DMD, base editing has been widely pursued to target many genetic or even non-genetic diseases, including hearing loss, blindness, immunodeficiency, cardiovascular diseases, blood disorders, heart failure, liver diseases, neurodegenerative diseases, and viral infection, among others. 10 Excitingly, the first in vivo base-editing clinical trial involving nonviral delivery of ABE targeting PCSK9 has shown promising initial results for the treatment of heterozygous familial hypercholesterolemia. 11 …”
Section: Main Textmentioning
confidence: 99%
“… 8 , 9 Besides DMD, base editing has been widely pursued to target many genetic or even non-genetic diseases, including hearing loss, blindness, immunodeficiency, cardiovascular diseases, blood disorders, heart failure, liver diseases, neurodegenerative diseases, and viral infection, among others. 10 Excitingly, the first in vivo base-editing clinical trial involving nonviral delivery of ABE targeting PCSK9 has shown promising initial results for the treatment of heterozygous familial hypercholesterolemia. 11 …”
Section: Main Textmentioning
confidence: 99%